HEALING DURATION OF SUPERFICIAL WOUNDS AFTER SUNNAH CUPPING THERAPY: A LITERATURE REVIEW - Isdianto, Andik; Fitrianti, Novariza (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Sunnah cupping therapy is widely recognized as a traditional treatment believed to eliminate stagnant blood, enhance circulation, and accelerate healing. However, concerns remain regarding wound depth and skin recovery duration, especially in clinical settings. This study aims to systematically review scientific literature on the healing duration of superficial wounds resulting from cupping, factors influencing recovery, and the effectiveness of herbal topical treatments in supporting natural skin regeneration. A systematic literature review was conducted using publications from 2015 to 2025 sourced from PubMed, Scopus, ScienceDirect, and Google Scholar. The analysis focused on non-surgical superficial wounds, post-cupping wound management, and the use of olive oil, black seed oil, and coconut oil in complementary traditional therapy. Findings indicate that cupping incisions typically reach only the epidermis and upper dermis, with a depth of 0.5–1 mm. These minor wounds generally heal within 3 to 7 days, depending on patient age, skin condition, anatomical location, and aftercare quality. The application of topical herbal agents has been shown to enhance healing through anti-inflammatory, antioxidant, and regenerative mechanisms. In conclusion, Sunnah cupping can be classified as a safe and non-invasive therapy with a relatively short healing duration. Herbal-based wound care offers a natural, accessible, and effective treatment alternative, supporting the integration of cupping therapy into modern evidence-based complementary medicine. Further development of standardized post-cupping care protocols is recommended to optimize clinical implementation and ensure consistent patient outcomes.